2017
DOI: 10.7251/ijeec1701036p
|View full text |Cite
|
Sign up to set email alerts
|

Development of an educational game based on IoT

Abstract: -Internet of Things (IoT) in combination with game based learning offers new possibilities to improve teaching and learning. This paper presents an example of using the IoT in education through the creation of an educational interactive game. An educational game based on the IoT has been developed. The developed system aims to motivate students to acquire and enhance knowledge in the field of IoT. The system is composed of a mobile application that serves as a controller for students, an administrative tool in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…IoT-based gaming devices usually consist of both hardware and software parts that provide a more realistic gaming experience. To improve teaching and learning, IoT in combination with game-based learning offers a new dimension and a wide range of possibilities (Petrović et al, 2017). Therefore, this research is focused on developing an IoT-based serious gaming platform for children with autism that will expedite the improvement of their cognitive skills.…”
Section: Related Workmentioning
confidence: 99%
“…IoT-based gaming devices usually consist of both hardware and software parts that provide a more realistic gaming experience. To improve teaching and learning, IoT in combination with game-based learning offers a new dimension and a wide range of possibilities (Petrović et al, 2017). Therefore, this research is focused on developing an IoT-based serious gaming platform for children with autism that will expedite the improvement of their cognitive skills.…”
Section: Related Workmentioning
confidence: 99%
“…The game design should meet requirements such as acceptability, challenge, clarity, interactivity, and reward [6]. On the other hand, technical conditions, as well as the integration with learning management systems (LMS), can be provided within smart classrooms [60,58]. The results have shown that students have achieved better learning outcomes by using educational games in a SLE [20,48,60].…”
Section: Educational Gamesmentioning
confidence: 99%
“…Additionally, with the development of SLEs, new forms of teaching approaches and aids have evolved, game-based learning being one of them [2,39,64]. As a form of entertainment created for stimulating the learning process, game-based learning relies on visual materials, didactics, and less formal styles of presentation to present knowledge in the form of a game [60,65]. The use of educational games is present in research papers and experiments, but it still has not been fully implemented in the teaching process in SLEs.…”
Section: Introductionmentioning
confidence: 99%
“…The largest number of studies on the use of mobile technologies in the field of education, conducted so far, has shown that these devices have a positive effect on learning efficiency in high schools and colleges. (Petrović, Stojanović, Labus, Bogdanović, & Despotović-Zrakić, 2017;Karabatzaki et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Today, the trend of using these tools in teaching is more and more present, as well as the growing interest of the academic community and the growth of the number of various researches related to these topics (Al-Bahrani & Patel, 2015;Petrović, Stojanović, & Labus, 2018;Domazet & Simović, 2020). The basic idea is to reach a level where mobile devices and applications are not considered a problem in the education process, but as a tool available to lecturers to improve educational practice (Stojanović, Bogdanović, Petrović, Mitrović, & Labus, 2020;Petrović, Jezdović, Stojanović, Bogdanović, & Despotović-Zrakić, 2017).…”
Section: Introductionmentioning
confidence: 99%